Colonic Phenotypes Are Associated with Poorer Response to Anti-TNF Therapies in Patients with IBD. Issue 8 (5th June 2017) - Yoon, Soon Man; Haritunians, Talin; Chhina, Sultan; Liu, Zhenqiu; Yang, Shaohong; Landers, Carol; Li, Dalin; Ye, Byong Duk; Shih, David; Vasiliauskas, Eric A.; Ippoliti, Andrew; Rabizadeh, Shervin; et al.
Abstract : Background: Although anti–tumor necrosis factor (TNF) agents are effective in patients with inflammatory bowel disease (IBD), many patients either do not respond to anti-TNF treatment or lose response over time. The aim of this study was to determine factors associated with response to anti-TNF therapy in IBD. Methods: Patients with Crohn's disease (CD) or ulcerative colitis who had consented to participate in a genetics registry and been treated with anti-TNF agents were evaluated retrospectively and categorized as primary nonresponders or secondary nonresponders. We evaluated clinical, serological, and genetic characteristics associated with primary nonresponse or time to loss of response to anti-TNF agents. Results: We included 314 CD (51 [16.2%] primary nonresponders and 179 [57.0%] secondary nonresponders) and 145 subjects with ulcerative colitis (43 [29.7%] primary nonresponders and 74 [51.0%] secondary nonresponders). Colonic involvement ( P = 0.017; odds ratio = 8.0) and anti-TNF monotherapy ( P = 0.017; odds ratio = 4.9) were associated in a multivariate analysis with primary nonresponse to anti-TNF agents in CD. In addition, higher anti–nuclear cytoplasmic antibody levels ( P = 0.019; hazard ratio = 1.01) in CD, anti–nuclear cytoplasmic antibody positivity ( P = 0.038; hazard ratio = 1.6) in ulcerative colitis, and a positive family history of IBD ( P = 0.044; hazard ratio = 1.3) in all patients with IBD were associated with time to loss of response to anti-TNF agents. Furthermore, various known IBD susceptibility single-nucleotide polymorphisms and additional variants in immune-mediated genes were shown to be associated with primary nonresponse or time to loss of response. Conclusions: Our results may help to optimize the use of anti-TNF agents in clinical practice and position these therapies appropriately as clinicians strive for a more personalized approach to managing IBD.